Child Street Life An Inside View of Hazards and Expectations of Street Children in Peru - Lieten, G.K.; Strehl, Talinay; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This brief studies the phenomenon of street children in two cities in Peru. It looks at some of the conceptual issues and, after analysing why children are in the street and what behaviour and which aspirations they exhibit, deals with the policy issues and lessons to be learned. This brief investigates when and why the transition from children on the street (street-working children) to children of the street (street living children) takes place and elucidates how they survive. It explains the fluidity and the risks involved in any type of child street life.
List of Tables -- 1 Victims and agency -- 2 Research and overview -- 3 Landing in the streets: a multiplicity of factors -- 4 Settling down in the street -- 5 Street child interventions and policies -- Conclusions and recommendations -- References.
Keywords: Social sciences; Medical research; Human rights; Childhood; Adolescence; Social groups; Quality of life; Social Sciences; Childhood, Adolescence and Society; Human Rights; Quality of Life Research; Electronic books